Numerical study of the generation and propagation of ultralow-frequency waves by artificial ionospheric F region modulation at different latitudes - Xu, Xiang (2016)
Powerful high-frequency (HF) radio waves can be used to efficiently modify the upper-ionospheric plasmas of the F region. The pressure gradient induced by modulated electron heating at ultralow-frequency (ULF) drives a local oscillating diamagnetic ring current source perpendicular to the ambient magnetic field, which can act as an antenna radiating ULF waves. In this paper, utilizing the HF heating model and the model of ULF wave generation and propagation, we investigate the effects of both the background ionospheric profiles at different latitudes in the daytime and nighttime ionosphere and the modulation frequency on the process of the HF modulated heating and the subsequent generation and propagation of artificial ULF waves. Firstly, based on a relation among the radiation efficiency of the ring current source, the size of the spatial distribution of the modulated electron temperature and the wavelength of ULF waves, we discuss the possibility of the effects of the background ionospheric parameters and the modulation frequency. Then the numerical simulations with both models are performed to demonstrate the prediction. Six different background parameters are used in the simulation, and they are from the International Reference Ionosphere (IRI-2012) model and the neutral atmosphere model (NRLMSISE-00), including the High Frequency Active Auroral Research Program (HAARP; 62.39°N, 145.15°W), Wuhan (30.52°N, 114.32°E) and Jicamarca (11.95°S, 76.87°W) at 02:00 and 14:00LT. A modulation frequency sweep is also used in the simulation. Finally, by analyzing the numerical results, we come to the following conclusions: in the nighttime ionosphere, the size of the spatial distribution of the modulated electron temperature and the ground magnitude of the magnetic field of ULF wave are larger, while the propagation loss due to Joule heating is smaller compared to the daytime ionosphere; the amplitude of the electron temperature oscillation decreases with latitude in the daytime ionosphere, while it increases with latitude in the nighttime ionosphere; both the electron temperature oscillation amplitude and the ground ULF wave magnitude decreases as the modulation frequency increases; when the electron temperature oscillation is fixed as input, the radiation efficiency of the ring current source is higher in the nighttime ionosphere than in the daytime ionosphere.